Modeling the robotics implementation barriers for construction projects in developing countries - Oke, A.E. (Emerald Group Holdings Ltd., 2021)
Purpose: The purpose of this paper is to evaluate the barriers militating against the adoption of robotics in the construction industry. Design/methodology/approach: Robotics implementation barriers were obtained from the previous studies and then through questionnaire survey construction stakeholders in Nigeria evaluate these barriers. Consequently, these barriers were examined via the exploratory factor analysis (EFA) technique. Furthermore, a model of these barriers was implemented by means of a partial least square structural equation modeling (PLS-SEM). Findings: The EFA results showed that these barriers could be categorized into two: cost and technology. Results obtained from the proposed model showed that platform tools were crucial tools for implementing cloud computing. Originality/value: The novelty of this research work will be provided a solid foundation for critically assessing and appreciating the different barriers affecting the adoption of robotics. Â© 2021, Emerald Publishing Limited.